2017
DOI: 10.29356/jmcs.v60i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polar Solutions on the Extraction of Phenolic Compounds from Capulín Fruits (Prunus serotina)

Abstract: <p>The phenolic compounds extraction of Prunus serotina Erhr with different ratios of acetone:water, methanol:water and ethanol:wa-ter was optimized using the Taguchi method. The factors evaluated were the solvent mixture and stirring time. The total phenolic content in extracts was assessed by the Folin-Ciocalteu method using gallic acid (GA) as the standard. The maximum value was 20.3 ± 0.86 mg <br />GAE g–1db using acetone:water (7:3, v/v) and 30 min of stirring time.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
2
6
0
3
Order By: Relevance
“…Herein, we used a mixed-method approach [19] integrating both qualitative and quantitative methods for sample collection, chemical analysis, correlation analysis, and result interpretation. Optimum ultrasonic extraction conditions efficiently obtained via Taguchi experiment design [20] was adopted for antioxidant extraction first. The preliminary chemical assay results were further confirmed by high-performance liquid chromatograph−photodiode array detector (HPLC-PAD) instrumental analysis and correlation analysis to find out the major active compounds and components causative to the AA.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we used a mixed-method approach [19] integrating both qualitative and quantitative methods for sample collection, chemical analysis, correlation analysis, and result interpretation. Optimum ultrasonic extraction conditions efficiently obtained via Taguchi experiment design [20] was adopted for antioxidant extraction first. The preliminary chemical assay results were further confirmed by high-performance liquid chromatograph−photodiode array detector (HPLC-PAD) instrumental analysis and correlation analysis to find out the major active compounds and components causative to the AA.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hassimotto [16] the main phenolic compounds present in the pulp of A. muricate are the catechins, highly soluble in polar solvents such as methanol. Hernández-Rodríguez [23] evaluated the effect of different solvents and extraction time on the extraction yield of total phenolic compounds in fruits of Prunus serotina Erhr, reporting however that there is not significant statistical difference using acetone-water (7:3 v/v) and methanol-water (4:1 v/v) while the optimal extraction time was 30 min. Several authors have reported the use of selective extractions for flavonoids, Henry-García [10] optimized the extraction process of flavonoids present in leaves of A. muricana, reporting an extraction efficiency of 87% using 96% ethanol as solvent.…”
Section: Discussionmentioning
confidence: 99%
“…Las muestras de fresa y cilantro previamente desinfectadas fueron extraídas de acuerdo con el método de (Hernández-Rodríguez et al, 2016). Primero se mezclaron con metanol al 80% en una relación 1/10 (p/v), ajustando el pH a 3 con HCl al 10%.…”
Section: Preparación De Extractosunclassified